2003
DOI: 10.1016/j.amjhyper.2003.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renin-angiotensin-aldosterone system gene variants on the severity of hypertension in patients with newly diagnosed hypertension

Abstract: A variant within the CYP11B2 locus has a clinically important impact on the severity of SBP changes in individuals with newly diagnosed hypertension who are of African ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 32 publications
2
19
0
3
Order By: Relevance
“…1 The mechanisms to explain the weaker correlations of cardiovascular indices and obesity in the African population remain unclear. But during the past few years genetic differences have been found regarding hypertension 23 and diabetes susceptibility, 24 as well as lipid levels 25 between the South African black population and the Caucasians who are from European descent. Because the present study aimed to exclude environmental influences when investigating this relationship, it is speculated that genetic differences regarding cardiovascular function in Africans (which have perhaps not been discovered yet) might be accountable for the effects observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…1 The mechanisms to explain the weaker correlations of cardiovascular indices and obesity in the African population remain unclear. But during the past few years genetic differences have been found regarding hypertension 23 and diabetes susceptibility, 24 as well as lipid levels 25 between the South African black population and the Caucasians who are from European descent. Because the present study aimed to exclude environmental influences when investigating this relationship, it is speculated that genetic differences regarding cardiovascular function in Africans (which have perhaps not been discovered yet) might be accountable for the effects observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphism of the aldosterone synthase gene, CYP11B2, is linked to a higher initial systolic BP in previously untreated black South Africans. 45 More of such studies are under way and may uncover other genetic changes in the enzymes controlling the RAAS system.…”
Section: Genes Controlling the Renin-angiotensinaldosterone Systemmentioning
confidence: 99%
“…Nevertheless, we did not find any evidence of association between AGT 235M/T polymorphism and the incidence of hypertension in our study population. Similarly, Rotimi et al [6] and Tiago et al [23] found no association between AGT 235M/T polymorphism and the hypertension in their study. But compared to the previous work, we obtained a higher frequency of the TT genotype in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Among the approaches used for searching for hypertension loci, few are linkage studies and most often are association studies [19]. The use of candidate gene approach includes the reninangiotensin system genes but given the ethnic diversity and the selection bias, the results from these studies are often faced with interpretation difficulties [20][21][22][23]. The uniqueness of this study lies in the fact that it is the first of its kind in the Burkinabe population that combines the RAS genes polymorphisms and the hypertension.…”
Section: Discussionmentioning
confidence: 99%